El derecho de libertad religiosa y su ejercicio entre centralización y descentralización territorial. Luces y sombras en la experiencia española (Stato, Chiese e pluralismo confessionale, 2023)
The right to religious freedom and its exercise between centralisation and self-goverment. Lights and shadows in the Spanish experience*ABSTRACT: The analysis of the regulation of religious freedom and its exercise in Spain, where a quasi-federal system of territorial distribution of power is in force, highlights the existence of regulatory disparities that cause differences in its exercise, hindering real equality in the enjoyment of this right. The removal of these obstacles requires twofold action. On the one hand, regulatory changes are needed to adapt the regulation of the exercise of religious freedom to the reality of a decentralised territorial model, so as to adapt the exercise of the right to the specific reality of religious diversity in each territory. But, on the other hand, it requires that equality of the basic conditions for the exercise of the right to religious freedom be guaranteed; which, in such a model, must be done through intergovernmental cooperation (in the so-called " Sectoral Conferences ").SUMARIO: 1. Introducción - 2. El desarrollo del derecho de libertad religiosa por la Ley Orgánica de libertad religiosa - 3. La regulación del ejercicio de la libertad religiosa en las comunidades autónomas. ¿Existe cooperación entre el Estado y las CCAA y de estas entre sí que garantice la igualdad en el ejercicio de la libertad religiosa? - 4. Comunidades autónomas y el ejercicio de la libertad religiosa - 5. Instrumentos de cooperación intergubernamental e interadministrativa - 6. Los Acuerdos con rango de ley con las confesiones religiosas en el sistema de fuentes.